Improving Learning Outcomes of Manipulative Basic Movements (Run-Throw-Catch) through Station Teaching Strategies in Grade III Students in Elementary School - Burhaein, Erick; Nursekha, Fuad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to improve basic manipulative movement skills, especially throwing and catching in 3rd grade students of SD N 1 Kalijirek Kebumen, through the application of station teaching strategies. The research method used is Classroom Action Research (PTK) which consists of two cycles. The design in this class action research uses the Kemmis & Mc. Taggart model where the stages consist of planning, implementation of actions, observation, and reflection. The research instrument used was an assessment of manipulative basic movement skills, while the data analysis used was quantitative and qualitative descriptive. The results of the study showed a significant improvement in students' motor skills. In the first cycle, the percentage of competency achievement was 50%, increasing to 87% in the second cycle, exceeding the Minimum Completeness Criteria (KKM). Thus, it can be concluded that the use of station teaching strategies can be applied effectively in manipulative movement learning activities in physical education. For subsequent research, it can use a wider range of materials as well as more diverse research methods and subjects